The properties of reconstituted panel manufactured from oil palm fronds / Chen Fung Woo and Suhaimi Muhammed - Chen, Fung Woo; Muhammed, Suhaimi (Universiti Teknologi MARA Cawangan Pahang, 2000)
The reconstituted panels were manufactured from oil palm fronds for different board densities (560 kg/m3 to 800 kg/m3) and tested for various properties such as modulus of rupture (MOR), modulus of elasticity (MOE) and thickness swelling. The modulus of rupture (MOR) of the board at 10% resin level was 27.3 MPa, 26.6 MPa, 47.5 MPa and 96.0 MPa at densities 560 kg/m3, 640 kg/m3 ,720 kg/m3 and 800 kg/m3 respectively. This is equivalent to 30% to 90% of the average equivalent solid wood. The boards retained 30% to 60% of their strength and 70% to 90% of their stiffness after soaking in water. Thickness swelling decreased from 51% to 23%, and water absorption decreased from 152% to 59% when board density increased from 560 kg/m3 to 800 kg/m3.